Tubo-ovarian abscess caused by Edwardsiella tarda: A case report - Kaitlyn Cox; Marci Crowley; Kimberly Fryer (Case Reports in Women's Health, 2022)
Tubo-ovarian abscesses (TOAs) are a complicated form of pelvic inflammatory disease (PID). They are usually caused by Bacteroides species or Escherichia coli. A 35-year-old woman presented with TOA caused by an infection with the rare pathogen Edwardsiella tarda. Thus, in a suspected case of a TOA in a patient with PID, we recommend obtaining a culture to test for a wide variety of bacterial organisms. By identifying less common pathogenic causes of TOA earlier, more conservative treatments can be used to mitigate the negative consequences of TOA and the need for surgical intervention.